EVALUASI PEMANFAATAN KOLEKSI REFERENSI PERPUSTAKAAN PDII-LIPI - Rachmawati, Rulina; Nashihuddin, Wahid; Anwar, Saiful (BACA: Jurnal Dokumentasi dan Informasi, 2017)
This study aims to: (1) describe the users’ profile of the reference collections in PDII-LIPI Library based on age, gender, education, knowledge, users’ experience; types and subjects of the reference collection which had been used by users; how to get the collection; and users’ purpose using the reference collections; (2) evaluate the utilization aspects of the reference collection that are reviewed based on ease of obtaining the reference collection; completeness of the reference collection; updated the reference collection; physical condition and arrangement of the reference collection; and the attitudes of officers in providing reference services to users. Data used in this study were quantitative, sourced from the questionnaire that were distributed to 100 respondents. Data were processed and analyzed using SPSS 23 software. The validity of the data was tested using Pearson Product Moment correlation and the reliability was tested using Alpha Cronbanch technique. Data that had been processed and tested then presented descriptively on graphs. From the distribution of questionnaires, only 51 respondents who filled out and returned the questionnaire to researchers, and these numbers were considered as valid and reliable. Results of the evaluation indicates that most of the reference collection users in PDII-LIPI Library are: (1) 20-25 years old, female, and from undergraduate background, use the reference collections by coming to the library or ordering via-email (through information searching services); (2) use journal collections for preparing their final project or research, such as undergraduate theses, graduate theses or doctoral dissertation; and (3) feel that the reference collections are very easy, complete, up to date, in a good physical condition and arrangement, and the attitude of the reference officers on serving to the users are good.